Boron laser doping using spin-on dopant for textured crystalline silicon solar cell. (15th May 2015) - Nishimura, Hideki; Manabe, Mitsuaki; Sakagawa, Hideki; Fuyuki, Takashi
Abstract: A novel precursor layer, polyboron film (PBF), was applied in the laser doping (LD) process. Localized LD using PBF was applied to a high-efficiency solar cell structure as a selective emitter (SE). Interface adhesion was improved by using an organic-polymer-based doping precursor, PBF. A strongly adhered interface contributed to the preservation of textured formations after disruption by LD, and to the homogeneous introduction of impurities. Surface geometries were retained almost completely even after LD. Sheet resistances were decreased by additional boron doping by LD. The photovoltaic characteristics were improved by SE formation using PBF with an optimum average laser power. Consequently, the SE formed by LD showed an increase in fill factor (FF), which contributed to the improvement in solar cell efficiency.